2004
DOI: 10.1207/s15324826an1101_7
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Health and Quality of Life in Minorities After Mild-to-Moderate Traumatic Brain Injury

Abstract: Much has been reported of the influence of age, affective symptoms, and satisfaction on self-ratings of health functioning, but little is known about the extent that race-based perceptions may have on influencing behavior or adjustment after a mild-to-moderate traumatic brain injury (MTBI). We investigated differences in perception of health functioning by race for mental and physical functioning using a global measure of health functioning. MTBI (n = 135) and general trauma (GT, n = 83) patients recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The known group analysis (Table 4) suggested the QOLIBRI scales are very sensitive to common TBI sequelae. 6,9,11,21,[60][61][62][63][64] Although consistent with other instruments assessing TBI by known groups, 7,9,61,65 this needs to be supported by responsiveness in a longitudinal study before QOLIBRI validation can be claimed. Importantly, change over time cannot be taken for granted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The known group analysis (Table 4) suggested the QOLIBRI scales are very sensitive to common TBI sequelae. 6,9,11,21,[60][61][62][63][64] Although consistent with other instruments assessing TBI by known groups, 7,9,61,65 this needs to be supported by responsiveness in a longitudinal study before QOLIBRI validation can be claimed. Importantly, change over time cannot be taken for granted.…”
Section: Discussionmentioning
confidence: 99%
“…Part A comprises four satisfaction scales: Cognition (7 items), Self (7), Daily life and autonomy (DLA; 7), and Social relationships (6). Part B, comprises two ''bothered'' scales: Emotions (5) and Physical problems (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Studies have also found worse self-reported functional outcomes among this racial group, even after adjusting for other demographic factors and injury severity. 30,31 These perplexing findings may relate to unmeasured sources of vulnerability to stress that are not ''factored out'' with statistical adjustment, cultural differences in interpretation of symptoms, or both. Future research might benefit from mixed-methods approaches to explore how people from different backgrounds perceive different symptoms and levels of functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, minorities with TBI have a longer wait time to see a physician [15], are less likely to be sent back to the referring physician after emergency department discharge [15] and tend to receive fewer therapy services (physical, occupational, speech and psychotherapy) during inpatient rehabilitation [9]. Moreover, minorities reported having significantly worse health and have less social support available to them after TBI [16]. In terms of functional outcomes, minorities have been found to have lower levels of social functioning and higher rates of alcohol abuse after TBI [17], with lower levels of social integration and community productivity after 1-year post injury [9,11,13,14].…”
Section: Introductionmentioning
confidence: 99%